Displacement and the Negotiation of Identity of Second Generation Immigrants in Black British Literature: The case of Andrea Levy’s The Fruit of the Lemon & Caryl Phillips’ In the Falling Snow - Mouissa Fattoum (My University, 2017)
The main concern of this dissertation is to draw a critical attention to the burgeoning field of Black British literature through the exploration of two contemporary Black British novelists namely Andrea Levy and Caryl Phillips. This study transcends the stereotypical and the Orientalist discourses which have elicited a critical interest in the last decades. Hence, this study is an attempt to uncover the tenets of hyphenated identities within the growing inquiry of belonging. Andrea Levy and Caryl Phillips are among the writers to offer critical insights on some of the conceived assumptions of belonging and identity formation. They are among the writers who led the campaign to reinvent Britain. Furthermore, these two novelists tried to make their people comprehend the mechanism behind their detachment, thus helping them how to be comfortably Black and British. Levy and Phillips, through their fiction, envision that identity is problematic for Black British people whose main problem refers to their inability to function and play their roles mainly with the encroachment of the main society. Additionally, both novelists insist on the importance of breaking out of intently conceived visions of ‘home’ and bridge the gap between ‘homeland’ and ‘outlan